TRAFFIC COMMUNITY EDUCATION EFFORTS THEN THROUGH COUNSELING IN PREVENTING TRAFFIC ACCIDENTS ON VICTIMS OF PRIVATE EMPLOYEES AT THE TEMANGGUNG POLICE STATION - Muhammad Ali (Advances in Police Science Research Journal, 2022)
This research was motivated by the problem of fluctuations in traffic accident cases in the jurisdiction of the Temanggung Police, most of the victims were private employees. So far Sat Lantas Polres Temanggung has handled the problem, but the results have not been maximized. Therefore, efforts to prevent traffic accidents through Dikmas Lantas counseling methods are carried out. According to this background, this study is aimed at explaining the picture of traffic accidents in the jurisdiction of the Temanggung Police And analyzing the efforts to organize the Lantas Dimas carried out through counseling in the prevention of traffic accidents of private employees in the jurisdiction of the Temanggung Police. Research is carried out by field research methods. The theoretical studies used in this research are management theory, social communication theory, social interaction theory, and several concepts such as the concept of effort, the concept of Dikmas Lantas, the concept of extension, the concept of prevention, the concept of traffic accidents and the concept of private employees. The results of this study showed that the problem of traffic accidents in Temanggung Was mostly experienced by victims with work identities as private employees. To overcome the problem of traffic accidents that have occurred so far, Dikmas Lantas has been implemented through counseling activities. However, in the implementation of the Dikmas counseling activities, there is no analysis of determining the right targets first, so that the results are not optimal, which can be observed from the implementation of Dikmas Lantas which has been carried out only focusing on organized communities on students only, while the implementation of Dikmas Lantas which is targeted at private employees is less planned so that the implementation of Dikmas Lantas which has been targeted at private employees is not carried out. For problem solving in the implementation of Dimas Lantas which is carried out through counseling, less obtaining budget support so that the implementation not optimal. Supposedly, an evaluation of the implementation of the Dikmas Lantas is needed so that budget distribution in the following years is not constrained, so that the implementation of Dikmas Lantas is optimal.